Strategi Pemasaran Usaha Produksi Tahu Dalam Meningkatkan Hasil Penjualan Menurut Perspektif Ekonomi Islam: (Studi Kasus Pabrik Tahu Pinta Lingkungan VII Pasar Sibuhuan Kecamatan Barumun) - Rizky Saputri Hasibuan; H. Amhar Maulana; Nur Jannah Nasution (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2024)
This thesis aims to: (1) To determine the marketing strategy of the tofu production business in increasing sales results according to an Islamic economic perspective at the Pinta Tofu Factory in Neighborhood VII, Sibuhuan Market, Barumun District. (2) To find out the advantages and disadvantages of marketing strategies used by Pinta Tofu Factory in Neighborhood VII, Sibuhuan Market, Barumun District. This research is a type of field research (field research), where this research uses qualitative research methods. The subjects in this study were the owners and employees of the Pinta tofu factory. Data collection techniques in this study were through observation, interviews and documentation. Data analysis techniques used in this research are data reduction, data presentation and conclusion drawing. The results showed that: (1) The marketing strategy applied by Pinta Tofu Factory is a market segmentation strategy, market positioning, differentiation and targeting. Then in the application of market segmentation, it suggests three segments such as psychographic segmentation, geographic segmentation and demographic segmentation. This is done so that it has a good impact on the business run by Mrs. Uba Roisa Lubis. (2) The advantages of choosing a location that makes the selling power of the Pinta Tofu Factory, having a strategic production site and directly marketing the products owned directly to traditional markets are also an attraction because it is easier for people to buy the products offered. While the shortcomings of the Pinta Tofu Factory are in capital problems in developing the business, the scarcity of production raw materials, namely soy beans, is also an obstacle in meeting public demand and the many competitors that appear in the target market by offering the same product.